«Единство в многообразии» как социально-политическая технология: перспективы и ограничения применимости в украинском контексте - Катруха, Евгений; Катруха, Євгеній; Katrukha, Evhenyi (My University, 2016)
В статье рассматривается возможность применения схемы «единство в многообразии» к решению проблемы раскола в украинском обществе. Для этого была проанализирована актуализация данной схемы в социологическом и политическом дискурсе. В качестве главной линии раскола рассматриваются языковая проблема и ее причины в контексте государственной политики и национальной идеи, анализируется степень сконструированности данной проблемы. Относительно «единства в многообразии» делается вывод о том, что данная схема применима к обществам с одной доминирующей культурой и для украинского общества схема нуждается в адаптации и конкретизации, а также должна сопровождаться реальным законодательным закреплением автономии регионов. Для дальнейших исследований представляется актуальным поиск конкретных вариантов данной схемы применительно к специфическим реалиям украинского общества. У статті розглянуто можливість застосування схеми «єдність у розмаїтті» для розв’язання проблеми розколу в українському суспільстві. Для цього проаналізовано актуалізацію цієї схеми в соціологічному та політичному дискурсі. У якості головної лінії розколу розглянуто мовну проблему та її причини в контексті державної політики й національної ідеї, проаналізовано ступінь сконструйованості. Щодо «єдності в розмаїтті» зроблено висновок, що ця схема може бути впроваджена в суспільства з однією домінуючою культурою та для українського суспільства повинна бути адаптована й конкретизована, а також має супроводжуватися реальним законодавчим закріпленням автономії регіонів. Для подальших досліджень убачаємо актуальним пошук конкретних варіантів цієї схеми, придатних до специфічних реалій українського суспільства. The topic of the article is the inter-regional break-up in Ukrainian community which can primarily be seen at cultural and socio-political levels. According to the author, one of its main causes is the limitation of rights of Russian-speaking people of Eastern Ukraine as well as the repression and pushing Russian language out of educational and public spheres. There has been revealed the imbalance between the real correlation of Russian and Ukrainian languages in the society and the adopted policy of introduction Ukrainian culture into life, as well as the ignoring the protests of Russian-speaking population against this policy, which brings the author to the conclusion that this break-up is not artificial but a natural one. As a possible solution of the problem there has been considered the "unity in diversity" scheme actualized in scientific and political discourse, which presumes that variety of cultures can be the foundation of unity of the country. The author has analyzed some scientific and journalistic articles which study the conception of unity in diversity. As a result, it has been revealed that this scheme is abstract and does not contain any mechanisms of its implementation. It has also been noticed that this scheme implies having cultural diversity around one main culture, which is not suitable for Ukrainian community that does not have this basic culture. Thus the author concludes that this scheme can be put into practice until after considerable improvement and specification which appears to be an urgent task for further research on this topic.
«Unity in diversity» as a Socio-Political Technology: Perspectives and Limitations Applicable in the Context of the Ukrainian
Keywords: единство в многообразии; раскол; политическая модель нации; этническая модель нации; полиэтничность; культурное разнообразие; єдність у розмаїтті; розкол; політична модель нації; етнічна модель нації; поліетнічність; культурне розмаїття; unity in diversity; break-up; political model of the nation; ethnic model of the nation; polyethnicity; cultural diversity